(untitled) (Laisvalaikio tyrimai, 2018)
New social-economic circumstances – market relations and stabilization of living level for the larger part of population demanded other attitude to the households, thus why today large attention is paid to the economic and behavioral moments in the research. According to this households are seen as one of the most important subjects in the economy on which results depends the welfare of each family and whole society. Nowadays it is more important than earlier to evaluate the living level and welfare of society in general and as a separate household, their material and social demographical groups. The relevance of the research is based on the growing importance of eco-tourism in the world and in the Russian Federation due to the development of this type of tourism and also due to the level of households economic development in rural area. Scientific innovation. The determination of the most socially and economically important features of households in the development of eco-tourism in rural areas is implemented as methods of adapting to the new conditions, as well as the development of a comprehensive theoretical and practical evidence-based recommendations for the development of the households in rural areas in the market eco-tourism services based on the analysis of economic practices, summarizing the literature, the study of foreign experience, identifying ways and sources of growth in key indicators of tourist activity of households. Practical innovation. Methods and approaches developed in this work could be recommended for use in the formation of regional and local strategic programs for the development of eco-tourism what will promote economic growth and improve the quality of life of the rural population of Russia. Scientific statements, conclusions and recommendations formulated in this work could be used by the executive authorities in the federal, regional and local levels to include complex programs in the development of practical measures in order to improve the quality of life of the rural population and ensure the conditions for a healthy lifestyle. The aim of the study is to develop methodological principles of eco-tourism development strategy in Russia, improving the economic performance of individual regions without alternative opportunities to improve the quality of life of the rural population and the level of environmental culture. Main trend is to improve the structure and efficiency of public investments in market innovations for the development of eco-tourism with the state support. Keywords: the process of eco-tourism, rural area, economy effect of households.